The Formal and Pragmatic Deficiencies of the Means of Constitutional Control in Mexico - Tapia Hernández, Erick Francisco (DIXI, 2021)
Purpose: In Mexico, there are three means of constitutional control; however, they have been surpassed in terms of their scope and protection due to the fact that there are acts of authority that are not regulated for their control or are expressly prohibited by law.Methodology: In this study, we will analyze the scope of the means of constitutional control, which are: constitutional controversies, actions of unconstitutionality and the amparo trial.Findings: We will notice that this is a complex issue to be raised in Mexico, both politically and legally, aggravated by the attempt to adapt somewhat obsolete or at least insufficient figures to the demands of a new system of constitutional justice that every constitutional State should have. This has contributed to the perception of uncertainty in the justice system in Mexico, both in law and in practice, by all the justice operators involved.Conclusions: In the development of this study, we have warned that the justice system for the defense of human rights in Mexico is deficient, particularly in terms of the means of constitutional control both in structure and in normative hypotheses that are absent and others that are even prohibited.
Keywords: amparo trial; unconstitutionality actions; constitutional control; constitutional controversies